Relações de emprego no campo: as diversas formas de contratação produtiva - FLEURY, Maria das Graças Prado (2010)
This is a dissertation wich main focus is the study, in the state of Goiás, of the employments relations in the field and its relateds.The disrespect to the workers rigths in the field has been perpetuated through the years. Only after the brasilian Constitution of 1988, rural and urban workers received the same legal treatment. The slavery that has been present for more than three hundred years can still be found through work practices that look like it.The arrival of the capitalist relations to rural area brougth more damage to the condition of the rural worker. The employment relation is a specie of the work relation itself and, to better contextualize it as a kind of subordinate service installment, different from the autonomous work and of other forms of subordinate service contribution, it is described the juridical discipline of the rural employment contract and of this other forms of service installment. In the last years, it was edited two laws creating specific rules to discipline the bond of rural employment. Both of them came from the fact that the demand of labor in the, nowadays, occurs in specific steps of production. The increase of productivity, caused by the modernization of agrarian activities raises the efficience of the system, but reduces the creation of employment. It does not necessarily implies the increase of work posts. Therefore, the biggest problem faced today, related to the emloyment in the rural area, is the bóia fria employee. Miguel Reale s Three dimension theory of Rigth sees the rigth as a normative integration of fact according to values. It allows an explainable analises of the rural employment problems, containing the elucidation of the conditions that came from the historical process and from the productive recovering, to, in the next step, analise the work law undestood in its three meanings: fact, value and norm, based in the constitutional principles of social function of the rural land and the dignity of human been. At the end, it is concluded that the question of work in the field goes far away from the work area. It depends of cultural changes and of the land distribution. Without a vision of the employee as a dignous human been, wich implies the fullfielment of the social function of the land, and without a better distribution of it, it is not possible to solve this problem. At last, it is analised the perspectives that shows themselves to the rural employees in Goiás. This dissertation is built up in three chapters. The first one, in which is related the history of Brasil and Goiás and a study about the production ways in this period. The second one, when the services types autonomous and subordinate - are characterized and is described the legal and judicial treatment, due to the expenditure of labor, in the various ways in which it is presented, focusing on the work of rural employees. The third chapter, in which is analyzed the situation of the rural employee, focusing the rural employee in Goiás, in view of the principles of social function of rural property and dignity of the human being, from the perspective of the Tridimensional Theory of Law of Miguel Reale.